Model Hasil Sedimen Pada Sungai Di Jawa - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
ABSTRACT: Research with a topic of "Sediment Yield Model on Rivers in lawn Island" which is based on secondary data from a master thesis program, will be used to identify the sediment yield of a river where no data are available. So the aim are to produced a sediment yield mode4 to know the relationship between the sediment yield and the biophysical factors and to know what is the dominant factor in that relationship on a river catchment. The first step of this research is to bring together data of catchments, than separate them due to fisiographic zones which are: Folded zone, Volcanic zone and Plato zone. After that normality test is applied into those data which consists of annual mean rainfall (P), catchment area (A), basin shape (Rf), basin length (Lb), average basin slope (Sb), length of main channel (Ls), slope of main channel (Ss), drainage density (Dd), settlement area (Apm), sawah area (As), dry-field area (At), forest area (Ah ), plantation area (Ap), area of soil-erosion (Ae), specific discharge (Qs), and sediment yield (S). The second step is to test the linear correlation and multiple regression to know the relationship between sediment yield (5) and the biophysical factors which affects the sediment yield either individually or in group for each physiography zones. The result of the analysis shows that separating data due to physiography gives a better application than the data which is not been separated for the sediment yield models. Biophysical environment factors which are dominant influence the sediment yield models are landuse especially settlements (Apm) and specific discharge (Qs).